PERANCANGAN SISTEM INFORMASI PENJUALAN PADA TOKO ROOSTER BROOD - Reynaldi Pantun Sianturi; Emma R. Simarmata; Resianta Perangin-angin (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2021)
In running a business, a system is needed that is able to support every operational activity of the business. Rooster Brood as one of the businesses in the culinary field that currently does not have a system that can work optimally, especially in the sales department. In the sales data management process, which still uses a recording system using a book, it can cause errors in inputting order data and other errors so that the resulting sales reports are not very accurate. The author in this case the opportunity to make a sales information system design based on the results of research that has been done. The design of this system is carried out using a programming language and several software with the aim of creating a system that provides information, input data and performs data management and produces reports that can be accessed easily through electronic devices. It is hoped that the design of this system can be useful for Rooster Brood in its business activities, especially in the sales department so that the data and information provided are more structured and accurate.